2020
DOI: 10.1116/6.0000226
|View full text |Cite
|
Sign up to set email alerts
|

Relating polymeric microparticle formulation to prevalence or distribution of fibronectin and poly-d-lysine to support mesenchymal stem cell growth

Abstract: Protein-coated polymer-based microparticles are attractive supports for cell delivery, but the interplay between microparticle properties, protein coating, and cell response is poorly understood. The interest in alternative microparticle formulations increases the need for a better understanding of how functional protein coatings form on different microparticles. In this work, microparticle formulations based on biodegradable polymers [poly (lactic-co-glycolic acid) (PLGA) and the triblock copolymer PLGA-polox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Optimization of the cell-carrier is therefore a key element to obtain effective cell adhesion. In this regard, we previously showed that the use of PDL allows interaction with FN, negatively charged, to facilitate its adsorption on the surface of the PAMs [22,23]. Another ECM protein was tested, vitronectin, which despite a higher protein coverage of the surface of PAMs compared to FN resulted in a diminished lEV adhesion (data not shown).…”
Section: Discussionmentioning
confidence: 98%
“…Optimization of the cell-carrier is therefore a key element to obtain effective cell adhesion. In this regard, we previously showed that the use of PDL allows interaction with FN, negatively charged, to facilitate its adsorption on the surface of the PAMs [22,23]. Another ECM protein was tested, vitronectin, which despite a higher protein coverage of the surface of PAMs compared to FN resulted in a diminished lEV adhesion (data not shown).…”
Section: Discussionmentioning
confidence: 98%
“…It must also be noted that the surface properties of PLGA microspheres can impact the effect of the coating. When propylene glycol is used instead of polyvinyl alcohol as the required surfactant during the preparation of PLGA microspheres, the coating distribution of the poly(D-lysine/fibulin) mixture and the subsequent attachment of MSCs are affected [ 98 ].…”
Section: Plga Scaffold Surface-modified Materialsmentioning
confidence: 99%
“…Polymers 2024, 16, x FOR PEER REVIEW 9 of 29 instead of polyvinyl alcohol as the required surfactant during the preparation of PLGA microspheres, the coating distribution of the poly(D-lysine/fibulin) mixture and the subsequent attachment of MSCs are affected [98]. Furthermore, a high-molecular-weight (Mw) poly-L-lysine (27.4 kDa, 36.6 kDa) may affect the metabolic activity of cells and it has a specific cytotoxicity [99], which is related to the inhibition of mitochondrial function [100].…”
Section: Polylysinementioning
confidence: 99%